Enhance household resilience in Istanbul - Kundak, Seda (Emerald, 2017)
Purpose This paper aims to address improvements in household preparedness against earthquake risks. Design/methodology/approach Two surveys were conducted in 2008 and 2013 to reveal prevention and preparedness measures which Istanbul’s inhabitants had taken in their households. Findings The findings of surveys show the progress in taking risk reduction measures which have been propagating from higher socio-economic status through all segments of the community in a five-year period. This shift is also evidence of the efficiency of community awareness programs conducted by governmental and non-governmental bodies in Istanbul. Originality/value The evaluation of the impacts of community awareness programs which leads the progress in risk reduction activities in Istanbul is a valuable example for large cities which are facing natural threats. The findings of this paper can be considered as a facilitator in understanding the tendency of different socio-economic groups against earthquake risk.